(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Chernenko I.A. Keywords: symbolic fable, Kafka, Suskind, hyperbole, art and artist, solitude, starvation, depth. The paper arguments the possibilities for comparative analysis of Kafka’s and Suskind’s short-story prose through specific representation of their aesthetics in the form of a symbolic fable. Special emphasis is paid to the composition and plot construction, which are closely connected with the estrangement effect disclosing the metaphorical formula of the writers: ‘Art is hunger’, ‘Art desires depth’.